CHARACTERISTICS AND ABUNDANCE OF MICROPLASTICS IN THE INTESTINES OF TIGER SHRIMP (Penaeus monodon) AT THE LARANGAN MARKET IN SIDOARJO - Aziz Ridho Fuady; Aunurohim Aunurohim (Journal of Marine-Earth Science and Technology, 2025)
Microplastic pollution has become an increasing environmental concern in aquatic ecosystems and is frequently detected in seafood consumed by humans. Several studies have documented microplastics in shrimp, but many rely mainly on visual identification or a single analytical method. As a result, detailed information on microplastic characteristics is still limited, particularly in shrimp sold for human consumption. This study investigated the characteristics and abundance of microplastics in the intestines of tiger shrimp (Penaeus monodon) obtained from Larangan Market, Sidoarjo, and considered their possible relevance to human exposure through seafood consumption. Twenty shrimp samples were analyzed, consisting of 10 males and 10 females with body lengths of 13–15 cm. Intestinal tissues were digested using 10% KOH at 60 °C for 24 hours and filtered using Whatman grade 42 filter paper (2.5 µm). Microplastics were identified according to their shape, size, and color using a stereo microscope equipped with Optilab imaging. Polymer composition was determined using Fourier Transform Infrared (FTIR) spectroscopy, while surface morphology was examined using Scanning Electron Microscopy (SEM). The use of these combined techniques allowed a more thorough identification of microplastics than approaches relying on a single method. Microplastics were detected in all shrimp samples, with an average abundance of 16.10 ± 3.75 particles per individual in males and 18.40 ± 6.60 particles per individual in females. The particles were mainly blue fragments measuring 10–50 µm, and FTIR analysis indicated nylon (polyamide, PA) as the dominant polymer type. SEM images also showed rough and irregular particle surfaces, suggesting that the detected particles were secondary microplastics produced by the fragmentation of larger plastic debris. These results provide additional evidence of microplastic contamination in P. monodon sold for human consumption in Sidoarjo and emphasize the importance of using multiple analytical techniques to better understand microplastic sources and their possible transfer to humans through seafood.